If you give a pig a pancake - Numeroff, Laura (New York : Scholastic, 1998)
If you give a pig a pancake, she'll want some syrup to go with it. You'll give her some of your favourite maple syrup, and she'll probably get all sticky, so she'll want to take a bath. She'll ask you for some bubbles. When you give her the bubbles...